Effectiveness of debt modification system in Korea - Kye Moon Lee; Junesuh Yi (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2023)
This study aims to examine the effectiveness of the debt modification system (DMS) in Korea. We find that DMS does have a positive effect in increasing the credit scores and annual income of DMS users. We also find that a debt management plan (DMP) is more effective in raising credit scores than personal rehabilitation (PR). However, the credit scores of DMS users in the first half of 2019 (551.1-626.1 points) are at a very low level, making it difficult to access low-interest unsecured loans from banks. Therefore, DMS in Kores is still insufficient to support the return of debt-ridden consumers to normal financial life and provide opportunities for a fresh start.
Keywords: G18; G20; G28; 330; Credit score; Debt management plan (DMP); Debt modification system; Fresh start; Personal rehabilitation (Chapter 13)